The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1097/00005768-200109000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of technique variations on knee biomechanics during the squat and leg press

Abstract: The greater muscle activity and knee forces in the squat compared with the LPL and LPH implies the squat may be more effective in muscle development but should be used cautiously in those with PCL and PF disorders, especially at greater knee flexion angles. Because all forces increased with knee flexion, training within the functional 0-50 degrees range may be efficacious for those whose goal is to minimize knee forces. The lack of ACL forces implies that all exercises may be effective during ACL rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
265
4
14

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(300 citation statements)
references
References 28 publications
17
265
4
14
Order By: Relevance
“…The difference in load response may be due to the different methods for estimating muscle co contraction. Similar to the current case however, (Escamilla et al, 2001) did not observe ACL forces dur ing simulated leg press and squatting exercises. (Cerulli et al, 2003) has measured in vivo ACL strain in a single male subject performing a rapid deceleration task, and found peak strains of 5.47 ± 0.28%, corresponding to the peak in vertical GRF.…”
Section: External Knee Loads For Optimized Simulationssupporting
confidence: 82%
See 1 more Smart Citation
“…The difference in load response may be due to the different methods for estimating muscle co contraction. Similar to the current case however, (Escamilla et al, 2001) did not observe ACL forces dur ing simulated leg press and squatting exercises. (Cerulli et al, 2003) has measured in vivo ACL strain in a single male subject performing a rapid deceleration task, and found peak strains of 5.47 ± 0.28%, corresponding to the peak in vertical GRF.…”
Section: External Knee Loads For Optimized Simulationssupporting
confidence: 82%
“…As noted earlier, net drawer force was obtained from the summation of the anterior-posterior resultant joint reaction force and the anterior-posterior force ac tions of the quadriceps and hamstring muscles. Similar methods have been used previously to provide estimates of ACL loading during skiing (Gerritsen et al, 1996), open and closed chain knee extension (Escamilla et al, 2001) and sidestep cutting (Simonsen et al, 2000). Con sidering that the ACL is the primary restraint to loading (anterior) in this plane (Butler et al, 1988), this repre sentation appears feasible.…”
Section: External Knee Loads For Optimized Simulationsmentioning
confidence: 96%
“…It is also important to note that the overall mechanical stress experienced at the knee may not be adequately described by the peak moment alone. Research has shown that compressive and shear forces at the knee increase with larger flexion angles and greater displacement of the femur relative to the tibia (11,24,28). As a result, it is expected that greater overall stress at the knee joint will occur during the traditional squat.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of its widespread use, the exercise has been the focus of a large number of biomechanical studies (10)(11)(12)19,21,23,24,28). The results present the squat as a complex movement that requires coordinated actions of the torso and all major joints of the lower extremities (10,20).…”
Section: Introductionmentioning
confidence: 99%
“…Open chain exercise increases anterior shear force and induces excessive tension of the anterior cruciate ligament 3) . On the other hand, closed chain exercise (CCE) does not cause anterior shear force because of the cooperative contraction of the quadriceps and the hamstring in the patellofemoral joint, and functional muscle recruitment patterns can be provided as many joints move 4,5) . CCEs to strengthen the quadriceps femoris muscle have been performed in various forms of exercises.…”
Section: Introductionmentioning
confidence: 99%